Humanization of care patients in hemodialysis programm - Cristina Maria Guedes Ferreira Moura; Helena Penaforte; Catarina Ribeiro; Catarina Sequeira; Maria Saraiva; Manuela Martins (Instituto Politécnico de Viseu, 2017)
Introduction: The design on the privacy in hemodialysis stresses that the person is a being in the world that has various dimensions, interacts with the environment and experiences unique experiences that mark their individuality. Objective: To identify the focus of attention on the practices of care for patients in regular hemodialysis program, guaranteeing respect for their individuality and privacy. Methods: resorted to the qualitative approach, following the precepts of fenomenografia, using semi-structured interviews with only one open question: Patients in Hemodialysis regular program have a medical, nursing and operational assistants to ensure respect for their individuality and privacy? Twelve health professionals were interviewed to perform functions in hemodialysis units, whose analysis and interpretation of the data presented as a focus the description of the qualitatively different meanings in variation dimensions. Results: Health care professionals reveal the preservation of the privacy of care in hemodialysis, in the care practices, translated by dimensions, physical space, body exposure, humanization of care and communication. Conclusions: In the perceived dimensions, on the preservation of privacy during procedures on hemodialysis, healthcare professionals value the focus of attention which by their nature and sequence invoke concerns over the implementation of the procedures. Respect for individuality and privacy are considered a basic human need to be promoted and their preservation is an important care to guarantee respect for patients on regular hemodialysis.